Tardigrada from Santo Antão Island (Archipelago of Cape Verde, West Africa) with the description of a new species - Fontoura, Paulo; Pilato, Giovanni; Lisi, Oscar (Zootaxa, 2011)
Three tardigrade species from Santo Antão Island, Archipelago of Cape Verde are firstly reported from Republic of Cape Verde: Echiniscus scabrospinosus Fontoura, 1982, Echiniscus clavispinosus sp. nov. and Milnesium tardigradum Doyère, 1840. E. clavispinosus sp. nov. belongs to the ‘viridis group’ of species characterized by the green colour and plate ornamentation comprised of tubercles, fine dots and light spots, by lacking dorsal and lateral trunk appendages (cirrus A excluded) and well developed claws. E. clavispinosus sp. nov. differs from all the known species of the ‘viridis group’ in having the area between the paired plate III and the terminal plate unsculptured, in details of the cuticular ornamentation, pointed clavae instead of papillate apices, and stronger spur on internal claws. A dichotomous key to the species of the Echiniscus viridis group and a list of Macaronesian species are also given.